Evaluation of Relative Yeast Cell Surface Hydrophobicity Measured by Flow Cytometry - Bryan Larsen; Michael Essmann; Richard N. Carter; Lisa Colling (Hindawi Limited, 2005)
Objective: To develop an efficient method for evaluating cell surface hydrophobicity and to apply the method to demonstrate the effects of fungal growth conditions on cell surface properties.